Microwave-assisted multicomponent reactions in heterocyclic chemistry and mechanistic aspects - Gulati, Shivani; John, Stephy Elza; Shankaraiah, Nagula (Beilstein Journal of Organic Chemistry, 2021)
Microwave-assisted (MWA) multicomponent reactions (MCRs) have successfully emerged as one of the useful tools in the synthesis of biologically relevant heterocycles. These reactions are strategically employed for the generation of a variety of heterocycles along with multiple point diversifications. Over the last few decades classical MCRs such as Ugi, Biginelli, etc. have witnessed enhanced yield and efficiency with microwave assistance. The highlights of MWA-MCRs are high yields, reduced reaction time, selectivity, atom economy and simpler purification techniques, such an approach can accelerate the drug discovery process. The present review focuses on the recent advances in MWA-MCRs and their mechanistic insights over the past decade and shed light on its advantage over the conventional approach.
Keywords: cycloaddition; Knoevenagel condensation; Michael addition; microwave; multicomponent reactions